Adakah Pengaruh Modal, Tenaga Kerja, dan Lama Usaha terhadap Pendapatan di IKM Kampoeng Batik, Sidoarjo? - Ana Toni Roby Candra Yudha; Muhammad Rendy Setiawan (Journal of Economics Development Issues, 2023)
This study aims to determine the effect of the capital, labor, and length of business and the dominant variable affecting Small and Medium Industries (IKM) income. This study uses a quantitative approach with a descriptive discussion. The test was carried out with multiple linear regression using SPSS with a total population of 30 using the accident sampling technique. The results of this study proved that capital and labor have a significant effect, while the length of business has no significant effect on IKM income. The dominantly influential variable is labor. These results provide information to IKM that they can better utilize technology, such as innovation in the batik production process for a cheaper price. Marketing of Batik Tulis Jetis can use social media or international e-commerce such as Instagram and Amazon to further increase income and be able to survive when on social restrictions due to the COVID-19 pandemic.